Sex-specific mortality of European shags after the Prestige oil spill: Demographic implications for the recovery of colonies - Martínez-Abraín, Alejandro; Velando, Alberto; Oro, Daniel; Genovart, Meritxell; Gerique, Cati; Bartolomé, Miguel; Villuendas, Elena; Sarzo, Blanca (Marine Ecology Progress Series, 2006)
Oil spills are extreme environmental perturbations (i.e. ecological catastrophes) affecting marine food webs and especially top predators, in which effects are likely amplified. As such, seabirds suffer from direct mortality and food depletion, with potentially important consequences for the population growth rate and probability of extinction. However, little is known about the effects of sex-skewed mortality (due to sex spatio-temporal differences in at-sea distribution) in seabird population dynamics. We analyzed the mortality of European shags Phalacrocorax aristotelis after the Prestige oil spill and its effects on breeding colonies in Galicia (southwest North Atlantic). Most adults found dead were females (85%). The year after the spill, Monte Carlo simulations of population trajectories predicted a reduction of 11% in the number of breeding pairs when skewed mortality was considered, and a lower rate (8%) when assuming random sex distribution of adult mortality. The further reduction predicted with the sex-biased mortality was probably the result of unmated adults unable to reproduce. This difference, although slight, is a concern for conservation owing that the colonies studied were already showing a 5% annual decline due to other factors also related to human activities. © Inter-Research 2006. Funds were partially provided by the Spanish Ministry of Science (grant ref. VEM2003-20052) Peer Reviewed